Memory, Ritual, and Identity in Ancient Greece and Rome - Panussi, Vassiliki; Hutton, William (Trends in Classics - Supplementary Volumes, 2025)
The essays in this volume consider the triptych of memory, ritual, and identity in ancient Greece and Rome. The issue of identity has recently dominated the arena of public discourse with renewed urgency, and in antiquity as in the current day, identities were created through an amalgamation of multivalent views and values. Individual identities were inextricably linked to collective identifications and informed by shared memories and experiences; these in turn shaped the narratives and practices that perpetuated connections within the community. Ritual played a foundational role in this process, as a deeply felt, iterative action that brought members of a community together to form powerful memories through which they negotiated their relationships with one another and with society at large. With contributions on ancient Greek and Roman literature, politics, religion, and material culture, and with a chronological scope ranging from archaic Greece to early Christendom, this volume examines the synergy of memory, ritual, and identity from multiple disciplinary perspectives and provides both an illustration of the variety of configurations that synergy took in Greco-Roman antiquity and how they persisted and evolved over time